Power-law index for velocity profiles in open channel flows - Cheng, Nian-Sheng (2012)
Turbulence theory has demonstrated that the log law is one of the established theoretical results for describing velocity profiles, which is in principle applicable for the near-bed overlap region, being less than about 20% of the flow depth. In comparison, the power law that is often presented in an empirical fashion could apply to larger fraction of the flow domain. However, limited information is available for evaluating the power-law exponent or index. This paper attempts to show that the power law can be derived as a first-order approximation to the log law, and its power-law index is computed as a function of the Reynolds number as well as the relative roughness height. The result obtained also coincides with the fact that the one-sixth power included in the Manning equation is of prevalent acceptance, while higher indexes would be required for flows over very rough boundaries.